The impact of diversity on the performance of work teams: A global study. - Michalička, Tomáš; Lančarič, Drahoslav; Nambuge, Dimuth; Munk, Michal (International Labour Review, 2025)
This article investigates the impact of various diversity dimensions and team characteristics on the performance of 911 sales teams within a multinational information technology company operating across 39 countries. Using stepwise regression analysis, the study finds that nationality diversity and job specialization diversity significantly enhance team performance, while greater diversity in first languages, larger team size, and longer managerial tenure negatively affect performance. Gender diversity, gender of the team manager, team members’ work experience, seniority, and team structure stability show no significant influence on team outcomes, which the authors attribute to the company’s active diversity management and standardized onboarding practices. The research highlights the importance of effective diversity management, inclusive leadership, and tailored training to leverage the benefits of diversity while mitigating challenges such as communication barriers and coordination difficulties. Limitations include the focus on a single industry and function, pre-pandemic data, and a one-year performance snapshot, suggesting avenues for future research on diversity’s evolving role in varied organizational contexts.